Export Competitiveness of Developing Countries and U.S. Trade Policy - Shushanik Hakobyan (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
We examine the impact of revocation of tariff exemptions on exports of developing countries, using data from the cases of Competitive Needs Limits (CNL) built into the Generalized System of Preferences (GSP). CNLs are arguably imposed on super competitive GSP beneficiaries and aim to limit their exporting capacity. We exploit the variation in the timing of the implementation of the CNLs across countries to identify the impact. We find that being excluded from the GSP due to a CNL induces a large and significant drop in imports from excluded countries, both in value and in their share in imports from all sources. Contrary to the policy objectives of CNLs, the excluded countries do not appear to be super competitive. In addition, we find some evidence of exporters increasing their exports of related products to the US after the CNL exclusion applies. Finally, our findings suggest that much of the benefits of CNLs accrue to non-GSP countries, rather than other GSP beneficiaries.
Keywords: F13; F14; O12; O19; 330; Generalized System of Preferences (GSP); Competitive Needs Limits; export competitiveness; trade policy; developing countries